Prassi di lavoro in una comunità terapeutica: un’esperienza - Madrucci, Matteo (Il sogno della farfalla, 2018)
The article deals with the issue relevant to the switch from an approach based on rehabilitation to an approach based on psychotherapy within the context of a NHS therapeutic community. By describing the history of the therapeutic community La chimera, in Grosseto, in Italy, the author outlines how the initial therapeutic programs were based on “doing”, and how this approach did not take the main relational dynamics that are fundamental for the community-based work into account. The article continues by describing the changes that have been gradually carried out within the community so as to set up an environment that favours group activities, the therapeutic milieu and the relational aspects of the therapy.